Predictors of smartphone's gaming addiction among Generation Z consumers: An empirical investigation from Pakistan - Saman Attiq; Hannan Afzal; Rauf-I-Azam; Hassan Jalil Shah (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
Smartphone games are played on smartphones, such as smartphones or feature phones; personal digital assistants; tablets that can handle gaming consoles; and portable media players with internet connectivity. People are becoming addicted to smartphone games. Few researches have examined such addiction's causes, including perceived social and psychological factors. Practitioners, researchers, and academics alike are keenly interested in examining the causes of smartphone gaming addiction. Thus, this study examines the antecedents of smartphone phone gaming addiction. Self-determination theory was used to propose a theoretical model, which was validated using partial least square structural equation modeling on 421 smartphone game players of Generation-Z. Data were collected through structured questionnaires. The study reveals that materialism, enjoyment, and peer pressure positively affect Generation-Z's psychological engagement and smartphone gaming addiction. This study also reveals that psychological engagement can act as mediator between materialism, enjoyment, peer pressure, and smartphone gaming addiction. These players eventually develop a smartphone gaming addiction because of various elements encouraging them to play smartphone games regularly. Businesses can benefit from understanding consumer behaviors related to smartphone use. This knowledge can be used for well-informed marketing strategies, product development, and customer engagement initiatives, recognizing the prevalence and potential consequences of smartphone addiction.
Keywords: 330; Smartphone gaming addiction; materialism; perceived enjoyment; peer pressure; psychological engagement; generation-Z